1995
DOI: 10.1152/jappl.1995.79.1.229
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vascular adaptations to augmented polycythemia during chronic hypoxia

Abstract: We previously found that augmentation of polycythemia by exogenous human recombinant erythropoietin (EPO) failed to worsen the severity of hypoxic pulmonary hypertension in rats. We asked whether this unexpected finding was related to reductions in cardiac output, left ventricular end-diastolic pressure, pulmonary vascular resistance, or some combination of these factors. Four groups of Sprague-Dawley rats were studied over a 3-wk period: hypoxic (0.5 ATM) and normoxic animals each injected with EPO (500 U/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
25
1
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 0 publications
4
25
1
1
Order By: Relevance
“…This supports the hypothesis that a gradual increase of hematocrit does not lead to a reduction of cardiac output as observed for acutely raised red cell volume. However, it should be kept in mind that the hematocrit of 0.63 in the experiments of Petit et al 13 was much lower than the hematocrit of our tg mice studied. Blood viscosity increases exponentially with hematocrit.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…This supports the hypothesis that a gradual increase of hematocrit does not lead to a reduction of cardiac output as observed for acutely raised red cell volume. However, it should be kept in mind that the hematocrit of 0.63 in the experiments of Petit et al 13 was much lower than the hematocrit of our tg mice studied. Blood viscosity increases exponentially with hematocrit.…”
Section: Discussioncontrasting
confidence: 57%
“…In rats, when hematocrit was raised over a 3-week period to a value of 0.63 by the administration of EPO 500 units thrice weekly, 13 mean arterial pressure, left ventricular end-diastolic pressure, right ventricular peak pressure, and cardiac output did not differ from the values in control animals (hematocrit 0.47). This supports the hypothesis that a gradual increase of hematocrit does not lead to a reduction of cardiac output as observed for acutely raised red cell volume.…”
Section: Discussionmentioning
confidence: 87%
“…The polycythemia in hypoxic rats by EPO administration did not worsen pulmonary hypertension but instead was associated with decreased vascular remodeling (40).The pathophysiology of hypoxic pulmonary hypertension is exceedingly complex and incompletely understood. As described in the Introduction, several genes whose protein products have been implicated in this process are induced by hypoxia and contain HIF-1 binding sites.…”
mentioning
confidence: 97%
“…20 In contrast, some investigators have reported that augmentation of polycythaemia by exogenous human recombinant erythropoietin failed to worsen the severity of hypoxic pulmonary hypertension in rats. 21,22 As none of the current patients had resting hypoxaemia, the possibility of secondary polycythaemia was very low.…”
Section: Discussionmentioning
confidence: 87%